Reactive extrusion glass fiber reinforced PA6 material and preparation method thereof
Through the reaction extrusion of lactam anion ring-opening polymerization method, combined with homemade TMI-g material as a catalyst and compatibilizer, the problems of large viscosity and low binding strength of existing glass fiber reinforced PA6 materials are solved, and the preparation of high-performance glass fiber reinforced PA6 materials is realized.
Patent Information
- Application Number
- CN202311269962.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing glass fiber reinforced PA6 materials have a high viscosity during the melting process, resulting in limited glass fiber addition ratio, and the physically blended glass fibers have low bond strength with the PA6 matrix, which is prone to phase separation.
Glass fiber reinforced PA6 material was prepared by reacting extrusion of anion ring-opening polymerization of lactam, and the homemade TMI-g material was used as a catalyst and a compatibility agent to make the lactam tightly polymerize and crystallize around the glass fiber.
The addition of high proportion of glass fiber has been achieved, the bonding strength between glass fiber and PA6 has been improved, and modified materials with excellent performance have been prepared, with a wider range of applications.
Smart Images

Figure BDA0004475282000000011 
Figure BDA0004475282000000061 
Figure FDA0004475281990000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to a reaction extruded glass fiber reinforced PA6 material and a preparation method thereof. Background Art
[0002] Nylon 6 is one of the most widely used engineering plastics. PA6 has high crystallinity, high melting point, excellent mechanical properties, good impact resistance, wear resistance and self-lubricating properties, and can be used in a variety of engineering plastic parts. Ordinary glass fiber reinforced modified PA6 is obtained by blending and modifying molten PA6 and glass fiber using a twin screw, but the viscosity of molten PA6 is relatively high, and the maximum addition ratio of glass fiber is about 50%. Moreover, the process is a simple physical blending, and the bonding strength between glass fiber and PA6 matrix is not high, and phase separation is easy to occur. Summary of the invention
[0003] In view of this, the present invention provides a reaction extrusion glass fiber reinforced PA6 material and a preparation method thereof to solve the problems raised in the above-mentioned background technology. The glass fiber reinforced PA6 material is prepared by the reaction extrusion anionic ring-opening polymerization of caprolactam, and the homemade TMI-g material is used as a catalyst and compatibilizer, so that caprolactam is tightly polymerized and crystallized around the glass fiber, thereby obtaining a modified material with excellent performance.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] On the one hand, the present invention discloses a reaction extruded glass fiber reinforced PA6 material, which is prepared from the following components in parts by weight:
[0006]
[0007] As a further solution of the present invention: the caprolactam is a crystalline raw material with a purity of 99.0% or more.
[0008] As a further solution of the present invention: the preparation method of the auxiliary agent TMI-g is as follows:
[0009] Under nitrogen protection, at 78°C-83°C, 3-isopropyl-dimethylbenzyl isocyanate and maleic anhydride were mixed in a mass ratio of 1:(1-3), heated, melted and stirred for 20-30 hours, cooled and crystallized, and the additive TMI-g was obtained.
[0010] As a further solution of the present invention: the glass fiber may be at least one of continuous glass fiber and chopped glass fiber.
[0011] As a further solution of the present invention: the initiator may be at least one of sodium hydroxide, initiator C10, and initiator C1.
[0012] As a further solution of the present invention: the antioxidant is at least one of a histamine-receptive antioxidant and a phosphite.
[0013] As a further solution of the present invention: the light stabilizer is at least one of a histamine light stabilizer and a hindered phenol light stabilizer.
[0014] Another aspect of the present invention discloses a method for preparing a reaction extruded glass fiber reinforced PA6 material as described in any one of the above, comprising the following steps:
[0015] Weigh each component according to weight, feed caprolactam, initiator, antioxidant and light stabilizer from the main feeding port of the twin-screw extruder, feed the auxiliary agent TMI-g from the side feeding port of the twin-screw extruder, and feed the glass fiber from the side feeding glass fiber port; the temperature of the first zone of the twin-screw extruder is 160°C-200°C, the second zone is 210-230°C, the third zone is 220-240°C, the fourth zone is 220-240°C, and the fifth zone is 210-230°C.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention prepares a glass fiber reinforced PA6 material by a method of reactive extrusion caprolactam anionic ring-opening polymerization. The present invention proposes a self-made TMI-g material for the first time. TMI is used as a catalyst for caprolactam anionic polymerization reaction. In the presence of a basic anionic initiator, the ring-opening polymerization of caprolactam can be initiated. Maleic anhydride itself has good compatibility with glass fiber. TMI-g can be used as a catalyst and a compatibilizer at the same time, so that caprolactam is closely polymerized and crystallized around the glass fiber, thereby obtaining a modified material with excellent performance. Since the viscosity of the caprolactam monomer after melting is very low, a high proportion of glass fiber can be added to prepare a glass fiber reinforced PA6 material with a wider range of applications. The preparation method of the present invention is to add caprolactam, glass fiber and initiator from the main feed, and add the auxiliary agent TMI-g from the side feed, which can ensure that the caprolactam contacts the catalyst after being completely melted, so that the polymerization is more uniform; and avoiding premature contact between the initiator and the catalyst can prevent the system from rapidly polymerizing and reduce the difficulty of processing. Different from traditional commercial nylon, the reaction extrusion preparation process of the present invention has greater room for adjusting the degree of polymerization, molecular weight and crystallinity through the adjustment of the formula, and the performance of the terminal products that can be prepared is wider, which has broad market application prospects. DETAILED DESCRIPTION
[0018] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0020] The specific information of the raw materials used in the following examples and comparative examples is as follows:
[0021] Caprolactam, brand name Henan Shenma, purity 99.0%;
[0022] Glass fiber 1: ECS305-3-K (Chongqing International); Glass fiber 2: ECS13-03-508A (China Jushi); Glass fiber 3: Continuous glass fiber-988A (China Jushi);
[0023] Initiator 1: sodium hydroxide; Initiator 2: Initiator C10 (Brueggemann); Initiator 3: Initiator C1 (Brueggemann);
[0024] Antioxidants, antioxidant 1098, antioxidant 168, BASF;
[0025] Light stabilizer 1: UV-3346 (Solvay); Light stabilizer 2: UV-329 (Rianlon); Light stabilizer 3: UV305 (BASF); Light stabilizer 4: Light stabilizer 4050 (BASF);
[0026] 3-Isopropyl-dimethylbenzyl isocyanate and maleic anhydride were purchased from Aladdin Reagents;
[0027] PA6, brand 3250 (Jiangsu Hongsheng).
[0028] All materials are commercially available conventional products.
[0029] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.
[0030] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0031] Example 1
[0032] Weigh 67.2 parts of caprolactam, 1 part of auxiliary agent TMI-g, 30 parts of glass fiber ECS305-3-K, 1 part of initiator sodium hydroxide, 0.2 parts of antioxidant 1098, 0.2 parts of antioxidant 168, and 0.4 parts of light stabilizer UV-3346 and add them into a twin-screw extruder for melt extrusion and granulation, wherein caprolactam, initiator, antioxidant 1098, antioxidant 168 and light stabilizer are fed from the main feeding port, glass fiber is fed from the glass fiber port, and auxiliary agent TMI-g is fed from the side feeding port. The temperature of zone 1 of the twin-screw extruder is 190°C, zone 2 is 220°C, zone 3 is 230°C, zone 4 is 230°C, and zone 5 is 220°C.
[0033] The preparation steps of additive TMI-g are as follows:
[0034] Under nitrogen protection at 80°C, 1 part of 3-isopropyl-dimethylbenzyl isocyanate and 2 parts of maleic anhydride were heated, melted and stirred for 24 hours, cooled and crystallized to obtain the additive TMI-g.
[0035] Example 2
[0036] Weigh 46 parts of caprolactam, 1.5 parts of auxiliary agent TMI-g, 50 parts of glass fiber ECS13-03-508A, 1.5 parts of initiator C10, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant 168, and 0.5 parts of light stabilizer UV-329 and add them into a twin-screw extruder for melt extrusion and granulation, wherein caprolactam, initiator, antioxidant and light stabilizer are fed from the main feeding port, glass fiber is fed from the glass fiber port, and auxiliary agent TMI-g is fed from the side feeding port. The temperature of the twin-screw extruder zone 1 is 190°C, zone 2 is 220°C, zone 3 is 230°C, zone 4 is 230°C, and zone 5 is 220°C.
[0037] The preparation steps of additive TMI-g are as follows:
[0038] Under nitrogen protection at 82°C, 1 part of 3-isopropyl-dimethylbenzyl isocyanate and 1 part of maleic anhydride were heated, melted and stirred for 25 hours, cooled and crystallized, and the additive TMI-g was obtained.
[0039] Example 3
[0040] Weigh 27.2 parts of caprolactam, 1.2 parts of auxiliary agent TMI-g, 70 parts of glass fiber ECS13-03-508A, 0.8 parts of initiator C1, 0.2 parts of antioxidant 1098, 0.2 parts of antioxidant 168, and 0.4 parts of light stabilizer UV-329 and add them into a twin-screw extruder for melt extrusion and granulation, wherein caprolactam, initiator, antioxidant and light stabilizer are fed from the main feeding port, glass fiber is fed from the glass fiber port, and auxiliary agent TMI-g is fed from the side feeding port. The temperature of zone 1 of the twin-screw extruder is 200°C, zone 2 is 220°C, zone 3 is 230°C, zone 4 is 220°C, and zone 5 is 220°C.
[0041] Under nitrogen protection at 80°C, 1 part of 3-isopropyl-dimethylbenzyl isocyanate and 2 parts of maleic anhydride were heated, melted and stirred for 26 hours, cooled and crystallized to obtain the additive TMI-g.
[0042] Example 4
[0043] 79.1 parts of caprolactam, 0.2 parts of auxiliary agent TMI-g, 20 parts of continuous glass fiber 988A, 0.3 parts of initiator sodium hydroxide, 0.2 parts of antioxidant 1098 and 0.2 parts of light stabilizer UV305 were weighed and added into a twin-screw extruder for melt extrusion and granulation, wherein caprolactam, initiator, antioxidant and light stabilizer were fed from the main feeding port, continuous glass fiber was fed from the glass fiber port, and auxiliary agent TMI-g was fed from the side feeding port. The temperature of the twin-screw extruder zone 1 was 160°C, zone 2 was 210°C, zone 3 was 220°C, zone 4 was 220°C, and zone 5 was 210°C.
[0044] Under nitrogen protection at 78°C, 1 part of 3-isopropyl-dimethylbenzyl isocyanate and 1 part of maleic anhydride were heated, melted and stirred for 20 hours, cooled and crystallized, and the additive TMI-g was obtained.
[0045] Example 5
[0046] 14.8 parts of caprolactam, 2 parts of auxiliary agent TMI-g, 80 parts of glass fiber ECS13-03-508A, 2 parts of initiator C10, 0.3 parts of antioxidant 1098, 0.3 parts of antioxidant 168, and 0.6 parts of light stabilizer 4050 were weighed and added into a twin-screw extruder for melt extrusion and granulation, wherein caprolactam, initiator, antioxidant and light stabilizer were fed from the main feeding port, the auxiliary agent TMI-g was fed from the side feeding port, and the glass fiber was fed from the glass fiber port. The temperature of the twin-screw extruder zone 1 was 200°C, zone 2 was 230°C, zone 3 was 240°C, zone 4 was 240°C, and zone 5 was 230°C.
[0047] Under nitrogen protection, 1 part of 3-isopropyl-dimethylbenzyl isocyanate and 3 parts of maleic anhydride were heated, melted and stirred for 30 hours at 83°C, and cooled and crystallized to obtain the additive TMI-g.
[0048] Comparative Example 1
[0049] 69.2 parts of PA6 3250 (Jiangsu Hongsheng), 30 parts of glass fiber-ECS305-3-K, 0.2 parts of antioxidant 1098, 0.2 parts of antioxidant 168, and 0.4 parts of light stabilizer UV-3346 were weighed and added into a twin-screw extruder for melt extrusion and granulation, wherein PA6, glass fiber, antioxidant and light stabilizer were fed from the main feeding port, and glass fiber was added from the side feeding glass fiber port. The temperature of the twin-screw extruder zone 1 was 190°C, zone 2 was 220°C, zone 3 was 230°C, zone 4 was 230°C, and zone 5 was 220°C.
[0050] Comparative Example 2
[0051] 49 parts of caprolactam PA6 3250 (Jiangsu Hongsheng), 50 parts of glass fiber ECS13-03-508A, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant 168, and 0.5 parts of light stabilizer UV-329 were weighed and added into a twin-screw extruder for melt extrusion and granulation, wherein PA6, initiator and light stabilizer were fed from the main feeding port, and glass fiber was added from the side feeding glass fiber port. The temperature of the twin-screw extruder zone 1 was 190°C, zone 2 was 220°C, zone 3 was 230°C, zone 4 was 230°C, and zone 5 was 220°C.
[0052] Comparative Example 3
[0053] 68.2 parts of PA6 3250 (Jiangsu Hongsheng), 30 parts of glass fiber-ECS305-3-K, 0.2 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.4 parts of light stabilizer UV-3346 and 1 part of compatibilizer POE-g were weighed and added into a twin-screw extruder for melt extrusion granulation, wherein PA6, antioxidant, light stabilizer and compatibilizer POE-g were fed from the main feeding port, and glass fiber was added from the side feeding glass fiber port; the temperature of the twin-screw extruder zone 1 was 190°C, zone 2 was 220°C, zone 3 was 230°C, zone 4 was 230°C, and zone 5 was 220°C.
[0054] Material performance tests of Examples 1-5 and Comparative Examples 1-2: The flame retardancy of the materials was measured according to the UL94 standard, the tensile strength was tested according to ISO 527 (test temperature 23°C), the flexural strength and flexural modulus were tested according to ISO 178 (test temperature 23°C), and the Izod notched impact strength was tested according to ISO 180 (test temperature 23°C). The results are shown in Table 1 below:
[0055] Table 1 Performance test results of the products obtained in each embodiment and comparative example
[0056]
[0057] It can be seen from the above table that the glass fiber reinforced PA6 product prepared by the present invention has higher mechanical properties than the molten glass fiber reinforced nylon product, and the maximum glass fiber content can reach 80%, which has a broader application space.
[0058] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0059] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.
Claims
1. A reaction extruded glass fiber reinforced PA6 material, characterized in that: It is prepared from the following components by weight:
2. The reaction extruded glass fiber reinforced PA6 material according to claim 1, characterized in that: The caprolactam is a crystalline raw material with a purity of 99.0% or more.
3. The reaction extruded glass fiber reinforced PA6 material according to claim 1, characterized in that: The preparation method of the auxiliary agent TMI-g is as follows: Under nitrogen protection, at 78°C-83°C, 3-isopropyl-dimethylbenzyl isocyanate and maleic anhydride were mixed in a mass ratio of 1:(1-3), heated, melted and stirred for 20-30 hours, cooled and crystallized, and the additive TMI-g was obtained.
4. The reaction extruded glass fiber reinforced PA6 material according to claim 1, characterized in that: The glass fiber may be at least one of continuous glass fiber and chopped glass fiber.
5. The reaction extruded glass fiber reinforced PA6 material according to claim 1, characterized in that: The initiator may be at least one of sodium hydroxide, initiator C10, and initiator C1.
6. The reaction extruded glass fiber reinforced PA6 material according to claim 1, characterized in that: The antioxidant is at least one of a histamine-receptive antioxidant and a phosphite.
7. The reaction extruded glass fiber reinforced PA6 material according to claim 1, characterized in that: The light stabilizer is at least one of a histamine light stabilizer and a hindered phenol light stabilizer.
8. The method for preparing the reaction extruded glass fiber reinforced PA6 material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh each component according to weight, feed caprolactam, initiator, antioxidant and light stabilizer from the main feeding port of the twin-screw extruder, feed the additive TMI-g from the side feeding port of the twin-screw extruder, and feed the glass fiber from the side feeding port of the glass fiber; The temperature of the twin-screw extruder zone 1 is 160-200°C, zone 2 is 210-230°C, zone 3 is 220-240°C, zone 4 is 220-240°C, and zone 5 is 210-230°C.
Citation Information
Patent Citations
High-welding-performance glass fiber reinforced polyamide composite material as well as preparation method and application thereof
CN103665844A
In-situ microfiber reinforced MC nylon composite material preparation method
CN109054029A
Method for preparing glass fiber reinforced nylon 6 material
CN1554528A